Changes in developmental rates of learning in young children with autistic spectrum disorders - Alessandri, Michael (2002)
The developmental rates of learning of 20 young children with autistic spectrum disorders were measured with a battery of learning, language, and adaptive behavior measures upon entry and exit from an early intervention program. These children received between 3 and 10 hours this highly structured program utilizing discrete trial teaching strategy. These final data support the hypothesis that behaviorally based early intervention can have an impact on developmental rates of learning of these young children with autism, that is both statistically and clinically significant.